MİFEPRİSTON MOLEKÜLÜ VE TÜREVLERİNİN ELEKTRONİK VE SPEKTROSKOPİK ÖZELLİKLERİNİN KUANTUM PROGRAMLAMA İLE İNCELENMESİ - KEBİROĞLU, MEHMET HANİFİ (Fırat Üniveristesi, 2023)
Biyolojik değerlendirme molekülü mifepristonun (RU-486) ayrıntılı moleküler ve atomik seviye özellikleri, hesaplamalı kimya yöntemleriyle araştırıldı. RU-486 ve varsayımsal türevleri (CH2CH3, CH3, F, Ph, KOH, NO2, OH) için yapısal, spektroskopik özellikler ve biyolojik uygulanabilirlik araştırıldı. Spektroskopik incelemede molekülün aktif bölgeleri, FTIR, NMR UV-VIS spektroskopisi, DOS ve Fukui fonksiyonları hesaplandı. Son olarak moleküler docking çalışmaları ile meme ve yumurtalık kanseri üzerindeki etkileri teorik olarak araştırılmıştır.

Detailed molecular and atomic level properties of the biological evaluation molecule mifepristone (RU-486) were investigated by computational chemistry methods. Structural, spectroscopic properties and biological applicability were investigated for RU-486 and its hypothetical derivatives (CH2CH3, CH3, F, Ph, KOH, NO2, OH). In the spectroscopic examination, active sites of the molecule, FTIR, NMR UV-VIS spectroscopy, DOS, and Fukui functions were calculated. Finally, the effects on breast and ovarian cancer were investigated theoretically with molecular docking studies.
Investigation of electronic and spectroscopic properties of mifepristone molecule and its derivatives by quantum programming
Keywords: Fizik ve Fizik Mühendisliği